Whither Al-Anbar Province? Five Scenarios Through 2011 - Bruce, James B. (RAND Corporation, 2010)
As U.S. forces withdraw from Iraq, significant changes can be expected throughout al-Anbar Province in security, political, economic, and even cultural relationships. RAND convened a series of three one-day workshops at which participants identified five relatively distinct futures, or scenarios, for al-Anbar that provide plausible but alternative trajectories for the province between early 2009 and the end of 2011.